Analysis of Barriers on Student Spin-Offs Intention - Abdul Rahman, Zahari; Puteri Fadzline, Muhamad Tamyez; Noor Azlinna, Azizan; Elinda, Esa (GBMR, 2018)
Purpose: This paper aims to investigate the effect of perception of barriers on student spin-offs intention and explores the question of whether the effect is varies according to demographic profiles. Design/methodology/approach: The data were collected using cluster sampling method. An online survey questionnaire was approached to respondents in eleven Malaysian public universities. Of these, 369 completed questionnaires were obtained for further analysis. Data was analysed using IBM Statistical Package for Social Science (SPSS) Statistics for Windows, Version 24.0. Few analyses such as descriptive analysis, reliability test, regression analysis, independent-samples t-test and analysis of variance were executed in this study